THE IMPACTS OF SERVICE QUALITY AND PERCEIVED VALUE TOWARD TELKOMSEL’S PREPAID SUBSCRIBERS SATISFACTION : A STUDY OF TELKOMSEL’S VIDEOMAX - Prasetya, Savitri Sekar; Fachira, Ira (Journal of Business and Management, 2017)
Abstract. Telkomsel launched VideoMAX in November 2016 to gain higher market share in a tight competition in telecommunication industry. The service is a data package contains video streaming quota to watch movies or TV series through video-on-demand applications (HOOQ & Viu).This study aims to explore Telkomsel’s prepaid subscribers satisfaction towards VideoMAX. Service quality and perceived value are assessed to evaluate customers’ satisfaction towards VideoMAX.Online & offline questionnaire are distributed to 384 respondents who is Telkomsel’s prepaid subscribers and have used VideoMAX with their domicile in Jabodetabek or Bandung. Multi linear regression (MLR) is used to analyse the impacts of service quality and perceived value towards customers’ satisfaction. The result is service quality and perceived have a significant impact towards customers’ satisfaction statistically. In addition, service quality and perceived value also positively influence customers’ satisfaction. Perceived value has more significant impacts towards customers’ satisfaction rather than service quality. Hence, in order to maintain or increase customers’ satisfaction towards VideoMAX, Telkomsel needs to improve perceived value first then followed by service quality. For further research, the coverage area of the research needs to be expanded into all over nation.Keywords : Customers’ Satisfaction, Mobile Value-Added Service, Perceived Value, Service Quality, Telecommunication Company